Motivos determinantes para la desaprobación del matrimonio homosexual en el Perú - Hernandez Pineda, William Alberto (2019)
ABSTRACT In the present investigation we sought to determine the determining factors for the disapproval of gay marriage in Peru. The study was descriptive. The population consisted of university students, parents of the departments of the Costa region, as well as the abundant national and international doctrine, legislation and jurisprudence. The sample consisted of a group of 350 students, parents of the Freedom, Lima, Piura and Arequipa, between 25 and 30 years of age, who belong or not to the LGBT community. The methods used were the hypothetical-deductive, the historical, dogmatic and systematic law, and the technique was the survey. To test the hypothesis formulated and fulfill the objectives of the investigation, it was used as a source that supports the Thesis, the analysis of the doctrine on Marriage between persons of the same sex and the legal norms applicable in national headquarters and comparative law. It was pointed out that there are substantial differences between the union of a man with a woman and the union of two people of the same sex. The main one of all is that the first union, being open by its own nature to procreation, has a public purpose that is the perpetuation of the species. The genital relationship between people of the same sex can never breed new human beings. Therefore, that there is a legal regulation called “marriage” for the first case and that said regulation cannot be applied to the second, in any way, means unfair discrimination in accordance with the doctrine and jurisprudence of the cited authors. The results show that in Peru, marriage is legally protected against same-sex unions, disagreeing that in the future, in Peru, the recognition of unions between people of the same must be legally and constitutionally protected. sex. The central conclusion is: the Constitution and the Civil Code do not incur discrimination in allowing marriage to only people of different sexes, because the principle of equality allows treating what is different, establishing that same-sex couples are different from those of different sex. Likewise, there is no discrimination because the principle of equality allows for justified differences to be instituted and, in the case of marriage, the difference is justified because it must be celebrated between a man and a woman.